Pengaruh Tingkat Perputaran Aktiva Lancar, Perputaran Modal Kerja, Likuiditas, Ukuran Perusahaan, Pertumbuhan Koperasi Terhadap Profitabilitas - Arimbawa, I Komang Tirta; Badera, Dewa Nyoman (E-Jurnal Akuntansi, 2018)
Cooperatives in Indonesia have important cooperative roles and benefits, because cooperatives can open the gates of Small and Medium Enterprises (SMEs) for the community, create an independent community, as a driver of the economy and create new jobs. Nevertheless, there are some problems in cooperatives, such as low human resources, difficulty in obtaining access to capital, and unprofessional management of cooperatives so that there are still many cooperatives that can not compete with other types of businesses and eventually become bankrupt. This can be bad because the cooperative is one of the pillars of the Indonesian economy. This study aims to empirically examine the influence of current asset turnover, working capital turnover,liquidity, firm size and cooperative growthability on profitability. This research was conducted on cooperative all-round business in Klungkung Regency in 2013-2015. Samples taken as many as 21 cooperative in 2013-2015, determined by purposive sampling method. Data was collected using documentation method. Analysis technique used is the Multiple Linear Regression Analysis. Based on the analysis results concluded that the current asset turnover rate, firm size and growth of cooperatives have a positive and significant impact on profitability, which means an increase in the current asset turnover, firm size and cooperative growth will also increase profitability. Meanwhile, working capital turnover and liquidity have a negative and significant effect on profitability, where the increase in working capital turnover and liquidity will decrease profitability. Keywords:   Current   Asset  Turnover,  Working  Capital,  Liquidity,  Firm  Size, Cooperative Growth,  Profitability